A Monopolistic Market for Advanced Traveller Information Systems and Road Use Efficiency - Rong Zhang; Erik T. Verhoef (Tinbergen Institute, 2004)
This study presents a model for exploring the interactions between a transport market and a monopolistic market for advanced traveller information systems (ATIS). We examine the properties of the information market, and in particular, the relationship between monopoly information pricing and road system efficiency. From model experiments, we find that increasing information penetration will lead to negative external effects for the already informed drivers. Furthermore, monopoly information pricing is not the most attractive option from a system efficiency viewpoint, because of the relatively high price charged by the monopolist. Third, a user or a producer subsidy on the information market can help realise a second-best optimum of road use. Finally, relatively low uncertainty on the road and high information costs limit the monopolist's profit on the information market, as well as relative system efficiency. While relatively inelastic demand for mobility negatively affects the monopolist's profit, the relative social benefits from private information peak at intermediate demand elasticities.
Keywords: R41; R48; D62; 330; Traffic congestion; traffic information; monopolistic pricing; Straßenverkehr; Information; Willingness to pay